新加坡海南会馆近30年（1980—今）： 中华文化传承初探 = Singapore Hainan Hwee Kuan and Chinese Culture : transmission and Inheritance (1980—Present) - 余巧云 Seah, Janice Qiao Yun (2012)
本文以两部分探讨新加坡海南会馆（后称会馆）近30年来在文化传承方面所作的努力。第一部分侧重简述会馆的历史及从1980至今所主办的文化活动，指出会馆的宗旨及旗下的活动一直围绕着中华文化的传承。本文将会馆策划的文化活动分成两个阶段进行探讨，首先是1980至2000年，会馆随着全国性的会馆复兴运动及国家重视文化的方策再次活跃起来，积极推动会务。另一个阶段是迈入21世纪时，会馆为了迎接新纪元而做出调整及改变。本文的第二部分会分析会馆30年来主办的文化活动究竟有何发展及特色。随着世界一体化会馆也开始走出新加坡，走向国际化，参与及主办多项国际形态的文化交流活动，与30年前相比大不相同。再者，因为文化传承需要下一代的参与，会馆不断以新颖的方式举办各类型的文化活动，成功吸引越来越多的年轻人参与，甚至成为会馆理事，渐渐解决青黄不接的状况。会馆成功地在不遗忘传统中华文的同时走出旧时代的框框，展望未来。This thesis delves into the efforts of Chinese culture transmission and inheritance by Singapore Hainan Hwee Kuan (Hwee Kuan) for the past 30 years. The first segment of the thesis focuses on the cultural activities organized by Hwee Kuan since 1980 and points out that the Hwee Kuan has always aimed to preserve and transmit Chinese culture. This thesis divides the cultural activities organized by Hwee Kuan into two parts, namely 1980 to 2000 where the renaissance of all clans in Singapore sparked a revival in Hwee Kuan's presence, and 2000 onwards where Hwee Kuan took a new approach in order to welcome the 21st century.